STOP TINDAKAN BULLYING MELALUI PENDEKATAN BEHAVIORAL DI PONDOK PESANTREN NURUL ISLAM DESA KARANG CEMPAKA KECAMATAN BLUTO KABUPATEN SUMENEP - Evi Dwi Hastri; Yudi Wibowo Sukinto; Muhammad Khalid Ali (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
The high number of bullying cases is already at an alarming stage. A school that is supposed to be a fun place, turns into a terrible place (school phobia), can even endanger the lives of students to the point of prolonged trauma. Bullying or Bullying does not look at age or distinguish genders, usually the victims of bullying are generally weak, quiet, shy, or special children. The bullying of bullying has a great influence until adulthood and during school period will cause depression in individuals and can also cause unhappy feelings when participating in activities at Pondok Pesantren, because it is haunted by feelings of anxiety and fear. So that this rule is found in Article 170 paragraphs (1) and (2) of the Criminal Code, Articles 351 to 355 of the Criminal Code, Article 80 of Law Number 35 of 2014 Amendments to Law Number 23 of 2002 concerning Child Protection. This problem is very complex so efforts are needed to suppress and overcome the occurrence of bullying or bullying that occurs in Santri at Islamic Boarding Schools through legal literacy and education, namely through a behavioral approach. Then what is produced can be supported by the implementation of the monitoring process from the Islamic Boarding School, in this case teacher educators or ustadz to prevent students from bullying. Then this monitoring is carried out periodically in diagnosing every behavior of students who tend and have the potential to violate the law to commit bullying actions.